Comunicação comunitária na política de comunicação organizacional: proposta de um protocolo de comunicação comunitária voltado aos territórios, às comunidades e aos modos de vida no Maranhão - SANTOS , Amarilis Cardoso (2021)
Originated from the author’s personal experience and feelings and based on the principle that communication is a human right, legitimate and guaranteed by the Brazilian State, this work aims to visualize the links between concepts and social practices, as well as the applicability in reality and particularity in Maranhão. Thus, the proposal is to present a Community Communication Protocol aimed at territories, communities and ways of life in Maranhão; a method of correlation between theory and practice based on the particularities of this territory, in order to become a possibility for the market to adopt and reapply. For this, we revisited the theories focused on study of organizational communication, community comunication and the alterity, especially through the Cicília Peruzzo’s academic legacy. An exploratory methodological path took place through a literature review and qualitative researchs, being the object of this investigation and reference for the protocol development, the Inhaúma, Coqueiro e Maruaí (São Luis rural zone) communities experiences, impacted by both the Aluminum Consortium of Maranhão - [Consórcio de Aluminio do Maranhao - ALUMAR] and Vale mining company. Makes sense, provide solution and contribute to the Maranhao’s Communiity Communication field are the objectives of this study when proposing to develop a Protocol as a contribution to professional practice from local contemplation.